Sustainable Economic Growth Through Green Finance: A Conceptual and Sectoral Analysis of Nepal - Rahman, Abdul (Madhesh Journal of Interdisciplinary Research, 2026)
Sustainable economic growth has become a key development priority for Nepal as the country seeks to balance economic expansion with environmental sustainability and climate resilience. In this context, green finance is increasingly recognized as an effective mechanism for channeling financial resources toward environmentally responsible and economically productive activities. The main objective of this study is to examine the role of green finance in promoting sustainable economic growth in Nepal. “Specifically, the study aims to analyze the application of green finance across selected economic sectors and to identify key challenges and opportunities in its implementation. The study adopts a conceptual and descriptive research design based on secondary data. Relevant information is collected from academic literature, government publications, reports of Nepal Rastra Bank, and international development agencies. A sectoral analysis approach is employed, focusing on selected sectors of the Nepalese economy, namely renewable energy, sustainable agriculture, eco-tourism, green infrastructure and transportation, and small and medium enterprises (SMEs). The findings reveal that green finance significantly supports sustainable economic growth by encouraging investment, employment generation, and environmental protection in the selected sectors. However, constraints such as limited financial awareness, institutional weaknesses, and insufficient access to long-term green financing persist. The study concludes that enhancing green financial instruments, strengthening regulatory frameworks, and promoting coordinated policy efforts are essential to maximize the contribution of green finance to sustainable economic growth in Nepal.